Gastro-oesophageal reflux symptoms, oesophagitis and Barrett's oesophagus in the general population: the Loiano–Monghidoro study. Issue 10 (18th April 2008) - Zagari, R M; Fuccio, L; Wallander, M-A; Johansson, S; Fiocca, R; Casanova, S; Farahmand, B Y; Winchester, C C; Roda, E; Bazzoli, F
Abstract : Objective: Existing endoscopy-based data on gastro-oesophageal reflux disease (GORD) in the general population are scarce. This study aimed to evaluate typical symptoms and complications of GORD, and their associated risk factors, in a representative sample of the Italian population. Methods: 1533 adults from two Italian villages were approached to undergo symptom assessment using a validated questionnaire and upper gastrointestinal endoscopy. Data were obtained from 1033 individuals (67.4% response rate). Results: The prevalence of reflux symptoms was 44.3%; 23.7% of the population experienced such symptoms on at least 2 days per week (frequent symptoms). The prevalence rates of oesophagitis and Barrett's oesophagus in the population were 11.8% and 1.3%, respectively. Both frequent (relative risk (RR) 2.6; 95% confidence interval (CI) 1.7 to 3.9) and infrequent (RR 1.9; 95% CI 1.2 to 3.0) reflux symptoms were associated with the presence of oesophagitis. No reflux symptoms were reported by 32.8% of individuals with oesophagitis and 46.2% of those with Barrett's oesophagus. Hiatus hernia was associated with frequent reflux symptoms and oesophagitis, and was present in 76.9% of those with Barrett's oesophagus. We found no association between body mass index and reflux symptoms or oesophagitis. Conclusions: GORD is common in Italy, but the prevalence of Barrett's oesophagus in the community is lower than has been reported in selected populations. Both frequent and infrequent reflux symptoms are associated with an increased risk of oesophagitis. Individuals with oesophagitis and Barrett's oesophagus often have no reflux symptoms.